Large-scale stationary hydrogen storage via liquid organic hydrogen carriers - Abdin, Zainul; Tang, Chunguang; Liu, Yun; Catchpole, Kylie (iScience, 2021)
Large-scale stationary hydrogen storage is critical if hydrogen is to fulfill its promise as a global energy carrier. While densified storage via compressed gas and liquid hydrogen is currently the dominant approach, liquid organic molecules have emerged as a favorable storage medium because of their desirable properties, such as low cost and compatibility with existing fuel transport infrastructure. This perspective article analytically investigates hydrogenation systems' technical and economic prospects using liquid organic hydrogen carriers (LOHCs) to store hydrogen at a large scale compared to densified storage technologies and circular hydrogen carriers (mainly ammonia and methanol). Our analysis of major system components indicates that the capital cost for liquid hydrogen storage is more than two times that for the gaseous approach and four times that for the LOHC approach. Ammonia and methanol could be attractive options as hydrogen carriers at a large scale because of their compatibility with existing liquid fuel infrastructure. However, their synthesis and decomposition are energy and capital intensive compared to LOHCs. Together with other properties such as safety, these factors make LOHCs a possible option for large-scale stationary hydrogen storage. In addition, hydrogen transportation via various approaches is briefly discussed. We end our discussions by identifying important directions for future research on LOHCs. [Display omitted] Chemistry; Energy flexibility; Energy Resources; Energy sustainability